Balancing exploration and exploitation across boundaries: Evidence from new product development - Marlon Fernandes Rodrigues Alves; Larissa Marchiori Pacheco; Simone Vasconcelos Ribeiro Galina (BRQ Business Research Quarterly, 2025)
Exploration and exploitation have opposite natures; therefore, balancing the two presents a key challenge for firms. Recent studies have argued that firms can combine exploration (exploitation) capabilities with exploitation (exploration) partnerships to surmount this obstacle. However, little is known about how accumulated capabilities for exploring and exploiting activities shape the ways in which firms select partnerships. We examine this question by leveraging a unique data set on new product development in the Brazilian manufacturing sector that has 19,081 observations over a 14-year span. Contrary to the expectation of complementarity, in which the greater capability of one type (e.g., exploitation) is associated with selecting a partnership of another type (e.g., exploration), our findings suggest that increases in capabilities of any type are associated with exploration partnerships. We provide alternative explanations for our findings, highlight implications for theory and practice, and discuss potential avenues for future research.
Keywords: O31; M13; L14; 650; Exploration; exploitation; ambidexterity; organizational learning; absorptive capacity; new product development